Cytokines in the Progression of Pancreatic β-Cell Dysfunction - Chunjiong Wang; Youfei Guan; Jichun Yang (International Journal of Endocrinology)
The dysfunction of pancreatic β-cell and the reduction in β-cell mass are the decisive events in the progression of type 2 diabetes. There is increasing evidence that cytokines play important roles in the procedure of β-cell failure. Cytokines, such as IL-1β, IFN-γ, TNF-α, leptin, resistin, adiponectin, and visfatin, have been shown to diversely regulate pancreatic β-cell function. Recently, islet-derived cytokine PANcreatic DERived factor (PANDER or FAM3B) has also been demonstrated to be a regulator of islet β-cell function. The change in cytokine profile in islet and plasma is associated with pancreatic β-cell dysfunction and apoptosis. In this paper, we summarize and discuss the recent studies on the effects of certain important cytokines on pancreatic β-cell function. The imbalance in deleterious and protective cytokines plays pivotal roles in the development and progression of pancreatic β-cell dysfunction under insulin-resistant conditions.